PENERAPAN CORE TAX ADMINISTRATION SYSTEM (CTAS) LANGKAH MENINGKATKAN KEPATUHAN PERPAJAKAN DI INDONESIA - Korat, Chevri; Munandar, Agus (Jurnal Riset Akuntansi Politala, 2025)
This literature review discusses how the implementation process of the Core Tax Administration System (CTAS) in Indonesia. This is an important step for efficiency, transparency and taxpayer compliance. The core tax is a technology-based tax system that is intended to control all tax administration process activities from registration, reporting, payment, collection of all taxes and supervision. Thus, a policy that underlies the implementation of the core tax is expected to be a major breakthrough. The existence of the core tax certainly makes it easier for the public to obtain information, tax reporting and the obligation to pay taxes itself. In addition, the core tax also facilitates control over the economy in various fields that have been quite difficult to overcome such as micro, small businesses, and the digital unit economy in Indonesia. However, in the implementation of this core tax there are several challenges and obstacles that must be faced, including obstacles to technological infrastructure, resistance to change, and data privacy issues. Indeed, with good management and education, the implementation of the core tax provides hope that it can simultaneously increase taxpayer compliance, increase the State Budget, and achieve economic development goals.